2012
DOI: 10.1186/1743-422x-9-76
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus-specific cellular immune responses in individuals with no evidence of infection

Abstract: The detection of hepatitis C virus (HCV)-specific T cell responses in HCV-uninfected, presumably unexposed, subjects could be due to an underestimation of the frequency of spontaneously resolving infections, as most acute HCV infections are clinically silent. To address this hypothesis, HCV-specific cellular immune responses were characterized, in individuals negative for an HCV PCR assay and humoral response, with (n = 32) or without (n = 33) risk of exposure to HCV. Uninfected volunteers (n = 20) with a chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…It is not clear whether the cellular response in exposed individuals is more frequent after stimulation with HCV core antigen (Della Bella et al 2005;Riviere et al 2012), or with non-structural antigens, in particular NS5 (Hashem et al 2011). Surprisingly, the virus-specific cellular response in non-infected individuals exposed to HCV is more frequent, stronger and directed against greater Proliferation assai (Cramp et al 1999) 16 (n = 14) CD4 ?…”
Section: Non-infected Individuals At Risk Of Exposure To Hcvmentioning
confidence: 94%
See 3 more Smart Citations
“…It is not clear whether the cellular response in exposed individuals is more frequent after stimulation with HCV core antigen (Della Bella et al 2005;Riviere et al 2012), or with non-structural antigens, in particular NS5 (Hashem et al 2011). Surprisingly, the virus-specific cellular response in non-infected individuals exposed to HCV is more frequent, stronger and directed against greater Proliferation assai (Cramp et al 1999) 16 (n = 14) CD4 ?…”
Section: Non-infected Individuals At Risk Of Exposure To Hcvmentioning
confidence: 94%
“…Different studies of HCV-specific cellular response among persistently infected individuals can be detectable in a surprising broad range from 12.5 to 69.0 % of Day et al 2002;Riviere et al 2012;Rosen et al 2002;Zhang et al 2009). Majority of studies report that the reactivity of CD4 ?…”
Section: Chronic Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies into the existence of transient HCV viremia have documented cases among individuals with high-risk exposures, such as HCWs [4] or prison inmates [5], [6]. Additionally, some studies have shown that subjects with high-risk exposure to HCV could induce cell-mediated immunity in the absence of detectable viremia or seroconversion, among HCWs [7], [8], people living with HCV-infected subjects [9], [10] and sexual partners of infected individuals [11], [12].…”
Section: Introductionmentioning
confidence: 99%